Assistance in Sustainable Food Programs Through the Introduction of Edible Plants as Potential Foodstuffs - Diana Hernawati; Vita Meylani; Rinaldi Rizal Putra; Dita Agustian (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
The purpose of this community service is to provide counseling about the introduction of edible plants that can be used and techniques or processing methods as an alternative food. Participatory Rural Appraisal (PRA) is used where the community is effectively involved in formulating plans and policies. Data collection is done directly in the form of primary and secondary data. At the same time, the data analysis technique is done by interactive analysis. The results of the service include 1) recognizing wild plant species as alternative food or plants that are always used as garden plants, 2) Potential edible plants that can be utilized can be in the form of leaves and stems or young stalks, roots, and tubers, fruits and vegetables. Nuts or seeds and grains; 3) It contains enough nutrients for nutritional needs and food supplements and health, both of which have the potential as internal and external drugs.